International trade and competition policy - Frederic Michael Scherer (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1996)
With the completion of the Uruguay Round of international trade negotiations, attention turns to plausible next steps. One question on the agenda of possibilities is the adoption of competition policies that complement or substitute for the remedies traditionally used to deal with international trade distortions. This paper examines three cases
Keywords: 330; industrial diamonds; potash from Saskatchewan; and cement from Greece; WTO-Regeln; Wettbewerbspolitik; Außenwirtschaft; Welt